Innovation and multidimensional entrepreneurship: Economic, social and academic aspects - Chrysanthi Balomenou; Konstantinos Kolovos (European Regional Science Association (ERSA), 2010)
This paper is divided into two parts, a theoretical and an empirical one and attempts to present Quality Management and the importance that it has in facing the international economic/ entrepreneurial competition. More particularly, in the first part of our paper are presented: -the significance of quality and main highlights of Total Quality Management -the history of Quality Management and the relevant literature (the theories of "guru" in the field of Total Quality Management, i.e. Edwards Deming, Joshep Juran, Philip Crosby, Kaoru Ishikawa and Armand Feingenbaum. Moreover, a special report is included in the work of Edwards Deming, as he is considered the father of Total Quality Management -the relations between customers / suppliers and the enterprises, the factors that add value in a product, and the importance of customer service is analyzed. The second part focuses on: -The significance of quality in the banking sector, and more specifically on the Model EFQM and its adoption by Hellenic Bank Public Company Ltd. -The highlighting of the structure of the aforementioned model, the levels of business excellence, the fundamental concepts for Quality Management and the RADAR method. -The case study of a greek bank and the achievement of the bank to be the first in the banking network in Greece that was honored with the "Committed to excellence" award on, -The research that was performed: in the above mentioned Bank with the use of questionnaires. This survey was supported by the nine criteria of EFQM Excellence Model. In the same chapter are presentated the conclusions on the changes in the philosophy of the bank by the adoption of model are indicated. in three banks with the use of questionnaires as well, and referred to customer services.
Keywords: 330; Quality Management; Business formation; Banking Sector